MO914: Development of Antibody Response to SARS-COV-2 Vaccines in Haemodialysis Patients. (3rd May 2022) - Fuessl, Louise; Lau, Tobias; Paal, Michael; Rau, Simon; Arend, Florian; Bruegel, Mathias; Fischereder, Michael; Schoenermarck, Ulf
Abstract: BACKGROUND AND AIMS: Previous data has shown a reduced immune response shortly after SARS-CoV-2 vaccinations in haemodialysis patients. We therefore investigated the long-term antibody response in patients from different outpatient dialysis centres at 4 weeks and 6 months after a complete vaccination against COVID-19. The results were compared with the humoral responses of non-dialysis subjects. METHODS: We designed a retrospective multicentric cohort study, enrolling 106 haemodialysis patients and 50 non-dialysis patients after the SARS-CoV-2 vaccination. SARS-CoV-2 antibody testing was performed as part of routine clinical practice 4 weeks as well as 6 months after the immunization with chemiluminescence immunoassays designed to detect antibodies against the SARS-CoV-2 spike protein (Elecsys Anti-SARS-CoV-2 S, Roche Diagnostics, Mannheim, Germany). Testing was performed in the Institute of Laboratory Medicine of the University Hospital Munich. According to the manufacturer's specifications, anti-SARS-CoV-2 S titres >0.8 U/mL are considered reactive (sensitivity 98.8% and specificity 99.9%). Anti-SARS-CoV-2 S titres < 100 U/mL were defined as a low antibody response. RESULTS: A total of 106 haemodialysis patients with a median age of 73 years received a SARS-CoV-2 vaccination ( n = 105 mRNA, n = 1 AstraZeneca). Of these, 50 non-dialysis patients with a median age of 56 years received a SARS-CoV-2 vaccination ( n = 45 mRNA, n = 5 mRNA/AstraZeneca). During the observational period, 8 haemodialysis patients and 2 non-dialysis patients additionally contracted a SARS-CoV-2 infection. Between the two testings, an overall decrease in anti-SARS-CoV-2 S antibody titres was observed (haemodialysis patients from a median of 252 to 95 U/mL, non-dialysis patients from a median of 1621 to 441 U/mL). At 6 months after the complete vaccination, 99 (93%) haemodialysis patients still presented with a detectable anti-SARS-CoV-2 spike antibody response (>0.8 U/mL), comparable to 100% of the non-dialysis subjects. However, 60 (57%) haemodialysis patients showed low antibody response (<100 U/mL), whereas only 5 (10%) non-dialysis patients presented with low antibody response. Patients with an additional infection showed an increased titre of antibodies during follow-up. CONCLUSIONS: Our data suggest regular antibody testing as well as a need for booster vaccination in the vulnerable population of haemodialysis patients.